2021
DOI: 10.1096/fj.202100549r
|View full text |Cite
|
Sign up to set email alerts
|

GSK‐3β inhibitor TDZD‐8 prevents reduction of aquaporin‐1 expression via activating autophagy under renal ischemia reperfusion injury

Abstract: Renal ischemia/reperfusion (I/R) injury is a main cause of acute kidney injury (AKI).Aquaporin (AQP)-1 water channel in the kidney is critical for the maintenance of water homeostasis and the urinary concentrating ability. Increasing evidence supports an important role of autophagy in the pathogenesis of AKI induced by renal I/R.The purpose of the present study is to investigate whether activation of autophagy prevents downregulation of AQP1 protein induced by renal I/R and potential molecular mechanisms. Rena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 50 publications
(121 reference statements)
0
12
0
Order By: Relevance
“…It can be observed in pathological conditions such as edema, and it also has an important role in kidney functions that require ltration [13]. AQP levels, which decrease in number due to damage to the kidney tissue for various reasons, may cause decreases in the ltration function of the kidney [14]. Selenium (Se) is an antioxidant and anti-in ammatory trace element [15].…”
Section: Introductionmentioning
confidence: 99%
“…It can be observed in pathological conditions such as edema, and it also has an important role in kidney functions that require ltration [13]. AQP levels, which decrease in number due to damage to the kidney tissue for various reasons, may cause decreases in the ltration function of the kidney [14]. Selenium (Se) is an antioxidant and anti-in ammatory trace element [15].…”
Section: Introductionmentioning
confidence: 99%
“…The induction of autophagy in kidney tubular cells, particularly in proximal tubular epithelial cells, has been documented in rodent models of I/R-induced AKI [3], although suppressed autophagy has also been observed [56,57]. Our recent study revealed that the induction of autophagy by TDZD-8 (a GSK-3β inhibitor) after I/R can rescue reduced AQP1 protein expression, likely by way of clearing deleterious factors (e.g., interleukin-1β) [58]. GSK-3β is known to modulate autophagy.…”
Section: Regulation Of Aquaporin 1 By Autophagy In the Kidneymentioning
confidence: 80%
“…GSK-3β overexpression activates the mammalian target of rapamycin complex 1 and suppresses autophagy, while its inhibition with inhibitors increases autophagic flux [59]. In vitro hypoxia/reoxygenation (H/ R) induced suppression of autophagy and downregulation of AQP1 in murine IMCD 3 cells expressing endogenous AQP1, which was fully prevented by TDZD-8 [58]. Interestingly, the inhibition of autophagy by 3-methyladenine or Atg5 gene knockdown attenuated the recovery of AQP1 protein expression induced by TDZD-8 in mIMCD3 cells with H/R.…”
Section: Regulation Of Aquaporin 1 By Autophagy In the Kidneymentioning
confidence: 99%
“…The SB202190 (Figure C, Table , 28 ) MAPK inhibitor promotes the transfer of TFEB and TFE3 from the cytoplasm to the nucleus and subsequently enhances autophagy and lysosomal biogenesis . As a potent, selective, and ATP-competitive inhibitor of GSK-3β, SB216763 (Figure C, Table , 29 ) and TDZD-8 (Figure C, Table , 30 ) have also been shown to activate autophagy. , Importantly, modulating bidirectional protein kinases can also alter autophagy. For example, SCH772984 (Figure C, Table , 31 ) is a new ERK1/2 inhibitor that induces autophagy in pancreatic cancer cells and may block active pancreatic stellate cells from senescence .…”
Section: Small-molecule Compounds Modulating Autophagy-related Kinasesmentioning
confidence: 99%